2018
DOI: 10.1038/s41598-018-34182-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary tuna hydrolysate modulates growth performance, immune response, intestinal morphology and resistance to Streptococcus iniae in juvenile barramundi, Lates calcarifer

Abstract: This study investigated the effects of tuna hydrolysate (TH) inclusion in fishmeal (FM) based diets on the growth performance, innate immune response, intestinal health and resistance to Streptococcus iniae infection in juvenile barramundi, Lates calcarifer. Five isonitrogenous and isoenergetic experimental diets were prepared with TH, replacing FM at levels of 0% (control) 5%, 10%, 15% and 20%, and fed fish to apparent satiation three times daily for 8 weeks. The results showed that fish fed diets containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 62 publications
12
84
2
3
Order By: Relevance
“…The protein availability and subsequent digestibility increased because of small polypeptide chains or short chains of amino acids that produced during the hydrolytic process (Silva, Rocha, Moreira, Signor, & Boscolo, ). Siddik, Howieson, Partridge, Fotedar, and Gholipourkanani () observed increased micromorphology of intestinal parameters such as fold height (hF), microvillous height (hMV) and external circumference of serosa (ECS) with the inclusion of PH in diets which could enhance growth performance of fish through increased nutrient uptake in more surface area, but Cahu, ZamboninoInfante, Quazuguel, and Gall () suggested the saturation of intestinal transport mechanisms by high luminal peptides and amino acids as a possible reason for inferior growth in some species. The appropriate level of PH supplementation can affect the improvement of growth indices (Siddik et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein availability and subsequent digestibility increased because of small polypeptide chains or short chains of amino acids that produced during the hydrolytic process (Silva, Rocha, Moreira, Signor, & Boscolo, ). Siddik, Howieson, Partridge, Fotedar, and Gholipourkanani () observed increased micromorphology of intestinal parameters such as fold height (hF), microvillous height (hMV) and external circumference of serosa (ECS) with the inclusion of PH in diets which could enhance growth performance of fish through increased nutrient uptake in more surface area, but Cahu, ZamboninoInfante, Quazuguel, and Gall () suggested the saturation of intestinal transport mechanisms by high luminal peptides and amino acids as a possible reason for inferior growth in some species. The appropriate level of PH supplementation can affect the improvement of growth indices (Siddik et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Siddik, Howieson, Partridge, Fotedar, and Gholipourkanani () observed increased micromorphology of intestinal parameters such as fold height (hF), microvillous height (hMV) and external circumference of serosa (ECS) with the inclusion of PH in diets which could enhance growth performance of fish through increased nutrient uptake in more surface area, but Cahu, ZamboninoInfante, Quazuguel, and Gall () suggested the saturation of intestinal transport mechanisms by high luminal peptides and amino acids as a possible reason for inferior growth in some species. The appropriate level of PH supplementation can affect the improvement of growth indices (Siddik et al, ). In addition, active peptides may be produced in the process of hydrolysis to enhance biological functions (Khosravi, Dio Bui, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches on FPH showed that a low or moderate amount of FPH may improve feed intake, growth and other performances of fish and shrimps (Hevrøy et al, ; Mamauag & Ragaza, ; Ospina‐Salazar, Ríos‐Durán, Toledo‐Cuevas, & Martínez‐Palacios, ; Valle et al, ; Wei, Liang, Mu, Zheng, & Xu, ; Xu, Mu, et al, ; Zheng, Xu, Qian, Liang, & Wang, ), while high levels of FPH often reduced fish growth performance (Mach & Nortvedt, ). The negative effects of high FPH levels on fish performance were mainly due to an excessive amount of AAs and peptides in the intestine, which could induce the saturation and competition of transporters mechanisms (Ospina‐Salazar et al, ; Siddik, Howieson, Partridge, Fotedar, & Gholipourkanani, ). In aforementioned studies, the results of growth performance were obtained based on dietary fishmeal replaced by FPH.…”
Section: Introductionmentioning
confidence: 99%
“…To incubate the cells for staining, the glass slide were placed in Giemsa solution for 20 min. Lysozyme (LYZ) activity was determined by the turbidimetric method described in Siddik et al (2018). Briefly, 5 mg of Micrococus lyso was mixed with 20 mL of PBS to prepare a bacterial suspension and stirred for 5 min.…”
Section: Immunological Indicesmentioning
confidence: 99%